Quantitative Survey of 3-alkyl-2-methoxypyrazines and First Confirmation of 3-ethyl-2-methoxypyrazine in South African Sauvignon blanc Wines - Alberts, P.; Kidd, M.; Stander, M.A.; Nieuwoudt, H.H.; Tredoux, A.G.J.; de Villiers, A. (South African Journal of Enology and Viticulture, 2016)
3-Alkyl-2-methoxypyrazines are important aroma components in Sauvignon blanc wine, contributing to the typical vegetative character associated with the cultivar. The analysis of methoxypyrazines is highly challenging and, as a result, limited quantitative data are available for South African Sauvignon blanc wines. In this study, liquid chromatography-tandem mass spectrometry was applied for the sensitive quantification of the three principal methoxypyrazines in 881 South African Sauvignon blanc wines. The total wine methoxypyrazine concentration exceeded the combined recognition threshold for the vegetative aroma in more than 60% of the samples, demonstrating the involvement of these compounds in the typical aroma of the cultivar. The analytical method was adapted to allow the accurate quantitation and spectral confirmation of 3-ethyl-2-methoxypyrazine in Sauvignon blanc wines for the first time. Concentrations ranged between 1.1 and 4.9 ng/L. Statistically significant relationships between wine methoxypyrazine concentrations and parameters related to the maturity of the grapes and to the climate, as well as geographical origin and vintage, were found.